BUILDING A SYSTEM OF INDICATORS FOR THE GEOLOGICAL AND ECONOMIC ASSESSMENT OF AN ENTERPRISE: AN INTERNATIONAL ASPECT - Aubakirova, Gulnara; Balakan, Islam; Issatayeva, Farida (SWorldJournal, 2025)
The export-oriented economy of Kazakhstan is characterized by all the features of emerging markets. The article demonstrates that for mining enterprises in Kazakhstan, operating in international markets, compliance with ESG principles and non-financial re